2003
DOI: 10.1002/rra.710
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic salmon (Salmo salar) in the regulated River Alta: effects of altered water temperature on parr growth

Abstract: The chief objective of this study was to analyse the effects of altered water temperature, due to the hydropower regulation of the River Alta, on growth of Atlantic salmon parr. The river was developed for hydroelectric purposes in 1987. A 110 m high concrete dam was built in the main river 49 km upstream from the outlet to the sea. The outlet of the power station is located 2.5 km downstream from the dam. The annual regime of water temperature has been altered downstream from the power station because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…They suggest that the basic, underlying timing of certain salmon life stages has a strong heritable component suggesting that local genetic adaptation may affect the timing of certain activities (Stewart et al, 2002). In the Girnock Burn, it has been shown that local genotype is a direct effect on growth performance (Jordan and Youngson, 1991), but, unsurprisingly, most of the variability in the growth of juvenile salmon (ca. 85%) can be accounted for by variability in stream temperatures (Bacon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggest that the basic, underlying timing of certain salmon life stages has a strong heritable component suggesting that local genetic adaptation may affect the timing of certain activities (Stewart et al, 2002). In the Girnock Burn, it has been shown that local genotype is a direct effect on growth performance (Jordan and Youngson, 1991), but, unsurprisingly, most of the variability in the growth of juvenile salmon (ca. 85%) can be accounted for by variability in stream temperatures (Bacon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…When high discharges do occur soon after hatch time (e.g. in 1997/1998 and 1999/2000) there may be marked effects on recruitment, foraging and growth rates (Jensen, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, gross variability in fish performance appeared consistent with inter-site variability in fry density where higher densities resulted in lower growth. This highlights one of the problems of investigating fish performance under field conditions where performance is often influenced by factors other than temperature, including density (as seen here) and food availability (Jensen, 2003;Bacon et al, 2005;Gurney et al, 2008). Such factors confound simple temperature-growth relationships, especially in short-term studies, where atypical conditions can confound parameter estimates.…”
Section: Juvenile Salmon Performancementioning
confidence: 92%
“…Minns et al, 1995;Gilvear et al, 2002), water temperature (e.g. McCarthy and Houlihan, 1996;Jensen, 2003), water quality (Winfield et al, 2004), predation (Gilvear et al, 2002), exploitation and management. A full literature review on the implications of climate change for Atlantic salmon forms part of the SWURVE project and is presented in Winfield et al (2004).…”
Section: Introductionmentioning
confidence: 99%